2016
DOI: 10.15406/mojpb.2016.04.00142
|View full text |Cite
|
Sign up to set email alerts
|

siRNA-based Nanoparticles for Cancer Therapy: Hurdles and Hopes

Abstract: In recent times, profound advances in therapeutic strategies for cancer therapy have been made. Most of these strategies including cationic polymers, small molecule inhibitors and monoclonal antibodies originating from the bench have resulted in successful translations to the bedside. One of these remarkable strategies was the potential of small interfering RNA (siRNA) to regulate gene expression by RNA interference (RNAi). An avalanche of research has indeed proven that RNAi is extremely essential in cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The specificity of action carried out by siRNA molecules depends upon the uniqueness of the selected sequences; however, many other factors may also have an impact on a lack of specificity 70. Several types involving siRNA off-target effects have been described and thoroughly reviewed 71.…”
Section: Off-target Effects and Stimulation Of Immune Responsementioning
confidence: 99%
“…The specificity of action carried out by siRNA molecules depends upon the uniqueness of the selected sequences; however, many other factors may also have an impact on a lack of specificity 70. Several types involving siRNA off-target effects have been described and thoroughly reviewed 71.…”
Section: Off-target Effects and Stimulation Of Immune Responsementioning
confidence: 99%
“…Although siRNAs are important in anticancer therapy, there are a number of extracellular and intracellular barriers that challenge their efficacy . Among these siRNA limitations, off-targeting, their instability in blood circulation, inadvertent stimulation of the host’s immune responses, as well as their incapability to enter cells (cell uptake) are the most important . With respect to off-targeting, it has been reported that one-tenth of siRNAs affect unintended genes .…”
Section: Sirna: Basics Role In Anticancer Therapy Challenges and Poss...mentioning
confidence: 99%
“…71 Among these siRNA limitations, offtargeting, their instability in blood circulation, inadvertent stimulation of the host's immune responses, as well as their incapability to enter cells (cell uptake) are the most important. 95 With respect to off-targeting, it has been reported that one-tenth of siRNAs affect unintended genes. 78 In addition, siRNAs triggers immunotoxicity by inducing inflammation and enhancing the levels of cytokines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The fate of successfully internalized siRNA were also greatly influenced by cell surface recycling, lysosomal degradation by lysozyme within cytosol and intracellular compartments release. All these criteria mentioned cause systemic delivery of siRNAs deemed challenging [ 28 , 29 , 30 ]. A growing number of studies have been implicated to develop safe and effective siRNA-targeted delivery systems with the means of utilizing viral and non-viral vehicles [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%